2004
DOI: 10.1002/ijc.20487
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism in the 5′ tandem repeat sequences of thymidylate synthase gene predicts for response to fluorouracil‐based chemotherapy in advanced colorectal cancer patients

Abstract: Thymidylate synthase (TS) is the primary target of 5-fluorouracil (5-FU).A VNTR polymorphism in the TS promoter region is associated with the efficacy of 5-FU-based chemotherapy in colorectal cancer. A common G>C SNP at the 12th nucleotide of the second repeat in the TS*3 alleles has been recently described. The combination of SNP and VNTR allows the definition of 3 TS alleles: *2, *3G and *3C. The aim of our study was to evaluate the predictive value of clinical response and survival of these new defined TS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
91
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 21 publications
9
91
1
1
Order By: Relevance
“…Therefore, the TS functional polymorphisms are under investigation for the possibility of optimising chemotherapy (Yong and Innocenti, 2007). Studies in patients with metastatic colorectal cancer showed that carriers of the TS 5 0 -UTR 3R (3G) and/or the TS 3 0 -UTR 6 þ alleles had adverse clinical outcomes (Pullarkat et al, 2001;Etienne et al, 2002;Park et al, 2002;Marcuello et al, 2004;Stoehlmacher et al, 2004;Martinez-Balibrea et al, 2007); however, such an association was not always detected (Lecomte et al, 2004;Jakobsen et al, 2005;Ruzzo et al, 2007a, b). Heterogeneity in clinical experimental conditions (Sorbye et al, 2007), in tumour burden (Köhne et al, 2002) and in genetic/molecular features in the presence of a multisite metastatic disease (Yokota, 2000) may explain variable results in these pharmacogenetic studies.…”
mentioning
confidence: 99%
“…Therefore, the TS functional polymorphisms are under investigation for the possibility of optimising chemotherapy (Yong and Innocenti, 2007). Studies in patients with metastatic colorectal cancer showed that carriers of the TS 5 0 -UTR 3R (3G) and/or the TS 3 0 -UTR 6 þ alleles had adverse clinical outcomes (Pullarkat et al, 2001;Etienne et al, 2002;Park et al, 2002;Marcuello et al, 2004;Stoehlmacher et al, 2004;Martinez-Balibrea et al, 2007); however, such an association was not always detected (Lecomte et al, 2004;Jakobsen et al, 2005;Ruzzo et al, 2007a, b). Heterogeneity in clinical experimental conditions (Sorbye et al, 2007), in tumour burden (Köhne et al, 2002) and in genetic/molecular features in the presence of a multisite metastatic disease (Yokota, 2000) may explain variable results in these pharmacogenetic studies.…”
mentioning
confidence: 99%
“…14 The 3R G > C has been shown to be present in approximately half of all Caucasian 3R alleles, and is commonly referred to as 3RC to distinguish it from the wild-type 3RG. 13 When both the VNTR and 3R G > C SNP are considered together, tumors from colorectal cancer patients with the homozygous wild-type 3RG/3RG genotype have been shown to have significantly higher TS expression compared to 2R/2R, 2R/3RC or 3RC/3RC individuals, 15,16 and patients with these low expression genotypes experience significantly higher rates of response and survival after 5-FU-based chemotherapy. 14,16 The C > G SNP in the last repeat of the 2R creates a second E-box consensus sequence and potential functional USF-binding site.…”
mentioning
confidence: 99%
“…13 When both the VNTR and 3R G > C SNP are considered together, tumors from colorectal cancer patients with the homozygous wild-type 3RG/3RG genotype have been shown to have significantly higher TS expression compared to 2R/2R, 2R/3RC or 3RC/3RC individuals, 15,16 and patients with these low expression genotypes experience significantly higher rates of response and survival after 5-FU-based chemotherapy. 14,16 The C > G SNP in the last repeat of the 2R creates a second E-box consensus sequence and potential functional USF-binding site. 14 In this case, the wild-type allele has been designated 2C and the variant 2G, however, in vitro studies have shown no functional difference between the two, and thus no further genotyping studies have been performed.…”
mentioning
confidence: 99%
“…Some groups showed that in general changes in non-coding DNA can have a tremendous impact on phenotype including drug response [27], disease susceptibility [28][29][30], and the evolution of differences between species [31]. In terms of odorant receptors in special, the dimension of influence by mutations in non-coding regions is not proved yet, and much more experiments and analysis will be required to draw conclusions how SNPs and odorant perception are related to each other.…”
Section: Resultsmentioning
confidence: 99%